2018
DOI: 10.1007/978-3-030-02366-9
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Intercalation in Bilayer Graphene Devices

Abstract: Bibliography Nyquist scattering time τq quantum lifetime τtr transport time θ contact angle U voltage UG gate voltage UOCV open circuit voltage Uxx, Uxy longitudinal and transverse voltage drop v, vD drift velocity vF Fermi velocity W width ξ valley index vi * Although higher values of |∆n| have successfully been achieved by this method, dielectric breakdown remains a fundamental limit to eld eect gating, making it dicult to reach values beyond |∆n| = 10 13 cm −2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 135 publications
(265 reference statements)
0
2
0
Order By: Relevance
“…Recently, the electrochemical intercalation for the controlled doping and material property tuning has been realized in filed effect transistor structures. For example, a bilayer graphene has been integrated into a miniaturized electrochemical cell architecture, and the intercalation process has been controlled through an electric gate 148 . Similarly, Yang et al has demonstrated gatetunable ionic intercalation in α-MoO 3 using ionic liquid-controlled transistor structures.…”
Section: Reversible Doping Of Layered Materials Through Gatecontrollementioning
confidence: 99%
“…Recently, the electrochemical intercalation for the controlled doping and material property tuning has been realized in filed effect transistor structures. For example, a bilayer graphene has been integrated into a miniaturized electrochemical cell architecture, and the intercalation process has been controlled through an electric gate 148 . Similarly, Yang et al has demonstrated gatetunable ionic intercalation in α-MoO 3 using ionic liquid-controlled transistor structures.…”
Section: Reversible Doping Of Layered Materials Through Gatecontrollementioning
confidence: 99%
“…The lithiation mechanism and lithium storage capacity of rGO have been the subject of numerous investigations by means of first-principle calculations and by experimental studies such as galvanostatic charge/discharge (GCD) measurements, cyclic voltammetry (CV), and differential capacity curves [69][70][71][72][73][74][75][76][77]. The theoretical capacity of graphene is 744 mAh g −1 if Li can be absorbed on both sides up to the chemical formula Li 2 C 6 , and 1116 mAh g −1 if Li can be trapped at the benzene rings up to LiC 2 , but these targets have not been achieved by using pure graphene materials [78].…”
Section: Lithiation Of Rgomentioning
confidence: 99%